SISTEM ANTRIAN PELAYANAN PASIEN PADA PUSKESMAS KELURAHAN SETIABUDI JAKARTA SELATAN DENGAN MENGGUNAKAN METODE WAITING LINE - Risa Wati (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2017)
Puskesmas is defined as a local government clinic for servicing society to be better for human’s health. It should provide an excellent service for society. By healing patients, absolutely, it will give the financial advantage for Puskesmas itself. There is Puskesmas Kelurahan Setiabudi. It has a lot of patients every single day, so that, it causes long-standing lines of patients. By recognizing that problem, a researcher here tries to solve it by using the method of Waiting Line. By providing the well-structured system of standing in line, hopefully, it is able to solve that current problem happened in Puskesmas Kelurahan Setiabudi.